Life cycle assessment (LCA) of electricity generation from rice husk in Malaysia - Mohd Shafie, Shafini; Mahlia, T.M.I.; Masjuki, H.H.; Rismanchi, B. (Elsevier Ltd., 2012)
his paper evaluated the life cycle analysis (LCA) of electricity derived from rice husk combustion in the Malaysia rice mills. Due to environment and security constraint cause by fossil fuel, biomass like rice husk becomes an attractive solution to look at. However, the environment profile of the electricity production from rice husk must be assessed to ensure it environment safety. The unit processes that make up the system are the paddy production, transportation to the rice mill, rice mill processing and combustion of rice husk to generate electricity. This study used functional unit as, 1.5MWh of electricity generating at the energy plant. The result show transportation contributes more to climate change compare to other process. Then, the characterized data from rice huskderived electricity is compared with coal and natural gas derived electricity. The results indicate the performance of rice husk derived-electricity is better in the aspect of environment impact parameters.